149 GEN-011: An ATLASTM-guided peripheral-blood derived neoantigen-specific T cell therapy designed to improve on TIL approaches. (10th December 2020) - Khare, Pranay; Zope, Harshal; Perry, James; DeVault, Victoria; Reuter, Mercay; Li, Adrienne; DeOliveira, Daniel; Lam, Hubert; Jain, Manish; Flechtner, Jessica; Khare, Pranay
Abstract : Background: In recent years, the FDA has approved engineered autologous T cell therapies with remarkable efficacy against hematological cancers. In addition, non-engineered tumor infiltrating lymphocyte (TIL) therapies have shown unprecedented benefit against solid tumors in early clinical trials. Despite their success, TIL products have limitations including the need for specialized surgery to obtain sterile tumor for T cells, low neoantigen breadth, and the potential for T cells that may be pro-tumor, exhausted, or not tumor-specific. These limitations may hinder efficacy and accessibility for certain patients. We have developed an autologous, peripheral blood-derived non-engineered T cell therapy, GEN-011, that embraces the advantages of TIL while improving on their limitations by targeting true tumor-specific neoantigens identified by the ATLAS TM bioassay and avoiding potentially pro-tumor Inhibigens TM . 1 Methods: Peripheral blood mononuclear cells and a tumor biopsy are collected from each subject; tumor DNA is sequenced by WES. The ATLAS bioassay is used to individually screen each tumor mutation with the patient's own T cells to identify neoantigen targets of pre-existing CD4 + and/or CD8 + T cell responses. The robust clinical scale manufacturing process, PLANET TM, expands the patient's peripheral blood T cells on ATLAS-identified stimulatory neoantigens. Results: The PLANET process produces GEN-011 drug products (DP) containing billions of antigen-specific, cytolytic T cells. Development and engineering runs using peripheral blood T cells from cancer patients and healthy donors resulted in DPs containing >97% T cells, >90% of which were central and effector memory phenotypes. A median 534-fold increase in antigen-specific T cells was observed in GEN-011 DPs over their starting frequency in peripheral blood with up to 67% of cells upregulating activation markers upon antigen recognition. Additionally, DP T cells secrete up to 50, 000 pg/mL of IFN-gamma in response to antigen stimulation. In cancer patient samples, DPs respond to up to 89% of intended neoantigen targets compared to <10% reported recently for TIL products. 2 3 Conclusions: GEN-011 is an autologous, neoantigen-specific T cell product, with key advantages over TIL therapy. First, GEN-011 has an unparalleled breadth of neoantigen coverage, targeting up to 30 relevant neoantigens with non-exhausted CD4 + and CD8 + memory T cells to overcome non-tumor specific 'passenger' T cells. Second, GEN-011 avoids pro-tumor Inhibigens that may be detrimental to clinical responses. Third, GEN-011 does not require extra surgery or viable tumor for manufacturing. In conclusion, GEN-011 is a first-in-class transformational T cell therapy candidate with characteristics that should improve accessibility and efficacy for patients with solid tumors. Ethics Approval: Informed consent was obtained from all individuals providing samples for this study. References: DeVault V, Starobinets H, Adhikari S, Singh S, Rinaldi S, Classon B, Flechtner J, Lam H. Inhibigens, personal neoantigens that drive suppressive T cell responses, abrogate protection of therapeutic anti-tumor vaccines. J. Immunol . 2020; 204(1 Supplement):91.15. Fraser H, Pike R, Thirkell S, Arshad A, Jide-Banwo S, Bartley H, Rologi E, Pruchniak M, Patel S, Mootien J, Robertson J, Craig A, Salm M, Newton K, Goodsell L, Chan F, Wilson G, Frenk S, Ali I, Peggs K, Lowdell MW, Del Rosio L, Hayes A, Turajlic S, Islam F, Lawrence D, Jamal-Hanjani M, Forster MD, Samuel E. The development of a personalized autologous clonal neoantigen T cell therapy for the treatment of solid cancer using the VELOS™ manufacturing platform generates highly potent and reactive CD8+ and CD4+ T cells for clinical use [abstract]. Virtual Annual Meeting II of the American Association for Cancer Research; 2020 Jun 22–24. Creelan B, Wang C, Teer J, Toloza E, Mullinax J, Yao J, Koomen J, Kim S, Chiappori A, Saller J, Tanvetyanon T, Landin AM, Fang B, Yu X, Saltos A, Thompson Z, Noyes D, Conejo-Garcia J, Chen T-D, Haura E, Antonia S. Durable complete responses to adoptive cell transfer using tumor infiltrating lymphocytes (TIL) in non-small cell lung cancer (NSCLC): a phase I trial [abstract]. Virtual Annual Meeting II of the American Association for Cancer Research; 2020 Jun 22–24.